Boosting biomass and leaf area with biol: morphological and yield responses of Pennisetum in the Peruvian highlands - Huaman Lizana, Darwin (2026)
The intensive use of chemical fertilizers in agriculture contributes to environmental pollution, which has driven the search for sustainable alternatives such as organic fertilizers. Among these, biofertilizer has garnered interest due to its potential to improve crop growth and yield. The objective of this study was to evaluate the effect of two types of biofertilizer: Bio Chumbinia (standardized) and traditional biofertilizer, as well as a control treatment (water), on the morphology, growth, yield, and leaf area of Maralfalfa (Pennisetum sp.). Morphological and growth variables were measured every 14 days, while yield and leaf area were evaluated in two successive periods corresponding to 42 days of growth. The results indicated that most morphological and growth parameters were significantly influenced by treatment, time, and evaluation (p < 0.05), except for tiller number, blade number, and the blade emergence rate (p > 0.05). Bio Chumbinia showed superior values compared with the control at 6.0 cm for plant height, 0.1 cm/day in the growth rate, 4.1 cm for blade length, and 1.2 mm for blade width; when compared with the traditional biol, the values were similar. The growth rate and leaf emergence peaked on day 14 and subsequently declined. The fresh and dry matter yields were consistently higher on Bio Chumbinia treatment than others (p < 0.05). Although no differences were found for blade weight and leaf area between Bio Chumbinia and the control, the leaf area in Bio Chumbinia was 1400 cm2 more than the control. The second evaluation showed improved productivity, which is consistent with the higher values on the morphological characteristics. No differences were observed in the leaf-to-stem + sheath dry matter ratio. These results demonstrate the potential of Bio Chumbinia to improve the productive performance of Maralfalfa as a foliar fertilizer in sustainable agricultural systems in Peru.